2021
DOI: 10.14309/ajg.0000000000001096
|View full text |Cite
|
Sign up to set email alerts
|

Previously Attempted Large Nonpedunculated Colorectal Polyps Are Effectively Managed by Endoscopic Mucosal Resection

Abstract: INTRODUCTION: Endoscopic mucosal resection (EMR) is an effective therapy for naive large nonpedunculated colorectal polyps (N-LNPCPs). The best approach for the treatment of previously attempted LNPCPs (PA-LNPCPs) is undetermined. METHODS: EMR performance for PA-LNPCPs was evaluated in a prospective observational cohort of LNPCPs ≥20 mm. Efficacy was measured by technical success (removal of all visible polypoid tissue during index EMR) and recurrence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…However, our data showed that operators in general agree about the settings for STSC. For STSC, universally, the soft coagulation mode is used with a current of 80 Watts and effect mode 4 on Erbe ENDO CUT Q 6 15 21 22 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our data showed that operators in general agree about the settings for STSC. For STSC, universally, the soft coagulation mode is used with a current of 80 Watts and effect mode 4 on Erbe ENDO CUT Q 6 15 21 22 23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, our data showed that operators in general agree about the settings for STSC. For STSC, universally, the soft coagulation mode is used with a current of 80 Watts and effect mode 4 on Erbe ENDO CUT Q [6,15,[21][22][23]. Settings for APC show more variation between operators, with currents between 30-70 Watts and a gasflow of 0.8-2.0 liters per min [18,19,24,25].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Additionally, operating time was not significantly longer in the recurrent lesions group, further pointing out the importance of this approach in overcoming the problems caused by fibrosis. In comparison, several studies have shown significantly increased technical difficulty, longer procedure times, and lower success rates for both EMR and ESD for recurrent lesions [13, 16]. Especially in the case of flexible ESD, some authors point out that only ESD experts should perform these difficult procedures, and the findings of studies in reference centres may not be generalized to all institutions [15].…”
Section: Discussionmentioning
confidence: 99%
“…These findings have now been reproduced in complex lesion subgroups, including LNPCPs involving the anorectal junction 8 and previously attempted LNPCPs. 9 Before thermal ablation, all visible polypoid tissue should be removed. Expose 1-2 mm of the snare-tip and gently apply it using snare-tip soft coagulation (Effect 4, 80 W: ERBE Electromedizin, Tubingen, Germany), aiming to create a 3-to 5-mm rim of ablated tissue around the complete resection defect.…”
Section: Thermal Ablation Of the Defect Marginmentioning
confidence: 99%